Pengembangan Keterampilan Mengajar dan Sosial Emosional Guru untuk Optimalisasi Pembelajaran - Fifi Juniarti (Syntax Corporation Indonesia, 2024)
This community service is conducted to address the needs of TK Regina Pacis teachers in understanding the basic principles and various aspects of child development. By understanding developmental stages and individual uniqueness, teachers will find it easier to apply appropriate strategies to support learning. This service is expected to serve as a means for developing teaching skills and social-emotional skills in teachers to enhance the learning process. The material covered includes basic theories about development, stages of early childhood development, and how teachers can develop useful strategies for managing their emotions. The activity is carried out in 3 face-to-face sessions using a lecture method, followed by discussions and role-play activities. All participants must fill in the evaluation form at the end of each session. Participants were also actively involved and provided positive feedback on the activity. Overall evaluations indicate that the activity went well, participants benefited, and the activity's objectives were achieved. This community service provides a good basic understanding of child development and serves as valuable learning for the participants. Continuous training related to psychological perspectives is considered important for educators and parents. Teachers felt the urgency to continually be equipped with insights and strategies from psychology to manage themselves and understand their students.